The effectiveness of a constructivist learning environment on learning in the high school science classroom. - Wooten, Vera (Curtin University, 1999)
This study hypothesized that students in a constructivist classroom would perform better academically than students in a traditionalist classroom. The methodology used was a multi~method approach utilizing both quantitative and qualitative techniques.Two separate classrooms of students in a 10th grade general science program were selected to serve as the experimental and control groups. One group was taught the material using traditional teaching methods in a traditional learning environment, functioning as the control group. The second group was taught the same basic material using constructivist methods in a constructivist learning environment.The most significant finding of the study was that students in the constructivist classroom scored higher on the achievement test than students in the more traditional classroom, even though constructivist approaches tend to focus on different assessment tools. Although the study lends support to the major hypothesis, it should be noted that further research must be conducted in this area. Samples of larger than 23 would ideally be chosen and more classes in multiple schools should be used. The use of a convenience sample; such as was done in this study, tends to limit the implication of the results, because the endings can only be strictly said to be true for classes in this particular school.